2021
DOI: 10.3390/rs13193836
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian U-Net: Estimating Uncertainty in Semantic Segmentation of Earth Observation Images

Abstract: In recent years, numerous deep learning techniques have been proposed to tackle the semantic segmentation of aerial and satellite images, increase trust in the leaderboards of main scientific contests and represent the current state-of-the-art. Nevertheless, despite their promising results, these state-of-the-art techniques are still unable to provide results with the level of accuracy sought in real applications, i.e., in operational settings. Thus, it is mandatory to qualify these segmentation results and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Samples from the posterior distribution approximated by such a model can be recovered quite easily by enabling the dropout layers not only at training time, but also at inference time. It has been shown that MC dropout can quantify model uncertainties well for remote sensing tasks like aerial image segmentation [38]. Recently, Hartmann et al [39] also successfully applied a Bayesian UNet for the segmentation of glaciers in SAR imagery.…”
Section: Quantifying Uncertainty With Contour Modelsmentioning
confidence: 99%
“…Samples from the posterior distribution approximated by such a model can be recovered quite easily by enabling the dropout layers not only at training time, but also at inference time. It has been shown that MC dropout can quantify model uncertainties well for remote sensing tasks like aerial image segmentation [38]. Recently, Hartmann et al [39] also successfully applied a Bayesian UNet for the segmentation of glaciers in SAR imagery.…”
Section: Quantifying Uncertainty With Contour Modelsmentioning
confidence: 99%
“…12 In general, solutions fall under two approaches: measuring DNN model-related uncertainty (i.e., epistemic uncertainty) and measuring data-related uncertainty (i.e., aleatoric uncertainty). 13 A representative technique for model-related uncertainty evaluation uses Bayesian neural networks, 12,14 which replace a single weight in the DNN with a probability distribution to produce a probabilistic prediction.The variation in model parameters can be translated to the variation in segmentation predictions, yielding an error margin for each pixel. Monte Carlo dropout 15,16 represents an alternative technique.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with its unique deep feature expression capacity, deep learning has provided new ideas for remote sensing image processing including semantic segmentation [12,13], object detection [14,15], image matching [16,17], etc. Many remote sensing image change detection methods based on deep learning have been proposed.…”
Section: Introductionmentioning
confidence: 99%